Generating a geospatial database of U.S. regional feedstock production for use in evaluating the environmental footprint of biofuels. (2nd April 2016) - Holder, Christopher T.; Cleland, Joshua C.; LeDuc, Stephen D.; Andereck, Zac; Hogan, Chris; Martin, Kristen M.
ABSTRACT: The potential environmental effects of increased U.S. biofuel production often vary depending upon the location and type of land used to produce biofuel feedstocks. However, complete, annual data are generally lacking regarding feedstock production by specific location. Corn is the dominant biofuel feedstock in the U.S., so here we present methods for estimating where bioethanol corn feedstock is grown annually and how much is used by U.S. ethanol biorefineries. We use geospatial software and publicly available data to map locations of biorefineries, estimate their corn feedstock requirements, and estimate the feedstock production locations and quantities. We combined these data and estimates into a Bioethanol Feedstock Geospatial Database (BFGD) for years 2005–2010. We evaluated the performance of the methods by assessing how well the feedstock geospatial model matched our estimates of locally-sourced feedstock demand. On average, the model met approximately 89 percent of the total estimated local feedstock demand across the studied years—within approximately 25-to-40 kilometers of the biorefinery in the majority of cases. We anticipate that these methods could be used for other years and feedstocks, and can be subsequently applied to estimate the environmental footprint of feedstock production. Implications : Methods used to develop the Bioethanol Feedstock Geospatial Database (BFGD) provide a means of estimating the amount and location of U.S. corn harvested for use as U.S. bioethanol feedstock. Such estimates of geospatial feedstock production may be used to evaluate environmental impacts of bioethanol production and to identify conservation priorities. The BFGD is available for 2005–2010, and the methods may be applied to additional years, locations, and potentially other biofuels and feedstocks.